Business Process Reengineering of Child Case Reporting and Approval Integrated With Weighted Triage - Harsoyo, Farras Sandy; Suharso, Wildan (P3M Politeknik Negeri Bengkalis, 2026)
This study aims to analyze and redesign the child case reporting and approval process at the Social Service Office of Batu City, which is still dominated by manual procedures. The Business Process Reengineering (BPR) approach is modeled using Business Process Model and Notation (BPMN) to identify process bottlenecks and formulate information technology–based solutions. Data were collected through field observations during an internship program, a review of standard operating procedures, and short interviews with officers, then validated through the development of a web-based prototype consisting of a reporting portal and an internal dashboard. The redesigned process includes the implementation of digital ticketing and queue status, early validation and duplicate checking, requests for data correction, weighted triage (P1–P3), as well as electronic approval and automatic issuance of assignment letters. Evaluation results show an increase in throughput efficiency from 56.41% and 40.74% to 86.96% and 89.29%, along with a reduction in process time from 78 to 23 minutes and from 108 to 28 minutes. This redesign accelerates service delivery, organizes queues, and improves traceability without changing existing SOP provisions.